Identification of HLA-A24-Restricted Novel T Cell Epitope Peptides Derived from P-Cadherin and Kinesin Family Member 20A. (19th June 2012) - Osawa, Ryuji; Tsunoda, Takuya; Yoshimura, Sachiko; Watanabe, Tomohisa; Miyazawa, Motoki; Tani, Masaji; Takeda, Kazuyoshi; Nakagawa, Hidewaki; Nakamura, Yusuke; Yamaue, Hiroki
Abstract : We here identified human leukocyte antigen-(HLA-)A ∗ 2402-restricted epitope peptides from Cadherin 3, type 1, P-cadherin (CDH3) and kinesin family member 20A (KIF20A) that were found to be specifically expressed in cancer cells through genome-wide expression profile analysis. CDH3-10-807 peptide and KIF20A-10-66 peptide successfully induced specific CTL clones, and these selectively responded to COS7 cells expressing both HLA-A ∗ 2402 and respective protein while did not respond to parental cells or COS7 cells expressing either HLA-A ∗ 2402 or respective protein. Furthermore, CTL clones responded to cancer cells that endogenously express HLA-A ∗ 2402 and respective protein, suggesting that CDH3-10-807 peptide and KIF20A-10-66 peptide are naturally presented on HLA-A ∗ 2402 molecule of human cancer cells. Our results demonstrated that CDH3-10-807 peptide and KIF20A-10-66 peptide are novel HLA-A24-restricted tumor-associated antigens and would be applicable for CTL-inducing cancer therapies.